The Effect of Third Party Funds and Non-Performing Financing on the Performance of Islamic Banks (Case Study at PT Bank Muamalat Indonesia Tbk) - Alamsyah, Malikul Hafiz (Budapest International Research and Critics University, 2021)
PT Bank Muamalat Indonesia Tbk. (“Bank Muamalat Indonesia”) is a financial institution that functions as a collector of funds from the public in the form of deposits and distributes them back to the public in the form of financing based on sharia principles. Sources of funds originating from public third party funds are in the form of Wadi'ah Current Accounts, Wadi’ah and Mudharabah Savings and Mudharabah Deposits. As a financial institution, the management of third party funds and redistribution in the form of financing will determine the bank's operating income, which in turn will affect the bank's financial performance which in this study is seen from profitability as measured by the Return on Assets (